Hindu history of Kashmir - Wilson, H. H. (Gurugram Spring, 2019)
This book is made up of three papers on the history and chronology of Kashmir based on Kalhana$1 (Bs great Sanskrit Kavya Rajatarangini, which contains nearly 8000 slokas. Besides Rajatarangini, the history of Kashmir is enshrined in three other Sanskrit works of Jonaraja, Srivasa, Prajyabhatta and Suka. Kalhana$1 (Bs Kavya brings down the narrative from traditional history to 1148 A.D., and the other writers who followed him continue the history to the date of the conquest of Kashmir by Akbar, 1588. The papers that these volumes comprise are : (i) (3z(Ban Essay on the Hindu History of Kashmir(3y (Bby H.H. Wilson, first published in the Asiatic Researches, Serampore, Vol. XV, 1825, pp. 1-119, (ii) (3z(BKings of Kashmir(3y (Bby R.C. Dutt,-Calcutta Review, July 1880, and (iii) Buhler$1 (Bs Report of a Tour in search of Sanskrit MSS made in Kashmir, Rajputana and Central India, -The Indian Antiquary, September, 1877.s
Keywords: India--Jammu and Kashmir; Hinduism